Reconstruction of 3D Shape for an Object using Laser Scanning Triangulation - Jawad, Hussain A.; Mahdee, Alaa S.; Mohamed, Nuha J. (Iraqi Journal of Laser, 2019)
This paper presents a method of designing and constructing a system capable of acquiringthe third dimension and reconstructs a 3D shape for an object from multi images of that object usingthe principle of active optical triangulation. The system consists of an illumination source, a photodetector, a movement mechanism and a PC, which is working as a controlling unit for the hard warecomponents and as an image processing unit for the object multi view raw images which must beprocessed to extract the third dimension. The result showed that the optical triangulation methodprovides a rapid mean for obtaining accurate and quantitative distance measurements. The finalresult's analysis refers to the necessity of using laser light in the active optical sensing technique forits unique characteristics.